Simplify -3/4r + 3 - 5/6r - 6.

1 answer

To simplify this expression, combine like terms:

-3/4r - 5/6r + 3 - 6

To combine the fractions, find a common denominator:

The least common multiple of 4 and 6 is 12.

-3/4r - 5/6r + 3 - 6 can be written as:

-9/12r - 10/12r - 3

Now, combine the "r" terms and the constant terms separately:

(-9/12r - 10/12r) + (3 - 6)

This simplifies to:

-19/12r - 3

So, the simplified expression is -19/12r - 3.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions